2019
DOI: 10.1002/hyp.13434
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal heterogeneity in soil water stable isotopic composition and its ecohydrologic implications in semiarid ecosystems

Abstract: Spatio‐temporal heterogeneity in soil water content is recognized as a common phenomenon, but heterogeneity in the hydrogen and oxygen isotope composition of soil water, which can reveal processes of water cycling within soils, has not been well studied. New advances are being driven by measurement approaches allowing sampling with high density in both space and time. Using in situ soil water vapour probe techniques, combined with conventional soil and plant water vacuum distillation extraction, we monitored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 68 publications
(104 reference statements)
4
64
0
Order By: Relevance
“…Understanding forest‐scale RWU strategies is critical for developing a process understanding of hydrologic responses to forest cover change. While individual‐ and stand‐level estimates of RWU strategies facilitated by stable isotopes in water and sap flux have become ubiquitous (e.g., Brinkmann et al, ; De Deurwaerder et al, ; Evaristo et al, ; Knighton, Conneely, et al, ), uncertainties in field methods and “scaling‐up” these findings to the catchment remain intractable problems (e.g., Oerter & Bowen, ; Penna et al, ). The metaanalysis of Evaristo and McDonnell () reviewed 531 studies of tree RWU derived from isotopes in water, of which 354 (~67%) used less than 10 xylem samples, possibly missing infrequent locations or periods of deep RWU.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding forest‐scale RWU strategies is critical for developing a process understanding of hydrologic responses to forest cover change. While individual‐ and stand‐level estimates of RWU strategies facilitated by stable isotopes in water and sap flux have become ubiquitous (e.g., Brinkmann et al, ; De Deurwaerder et al, ; Evaristo et al, ; Knighton, Conneely, et al, ), uncertainties in field methods and “scaling‐up” these findings to the catchment remain intractable problems (e.g., Oerter & Bowen, ; Penna et al, ). The metaanalysis of Evaristo and McDonnell () reviewed 531 studies of tree RWU derived from isotopes in water, of which 354 (~67%) used less than 10 xylem samples, possibly missing infrequent locations or periods of deep RWU.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the water stored in soil rock fragments can have an isotopic composition distinct to that of soil water or groundwater, being either relatively more depleted (in the case of δ 2 H in Oshun et al, 2015) or more enriched (Palacio et al, 2014;Rong et al, 2011). Such variable and contrasted isotopic effects of lithology are to be expected for differing minerals and can even cause fractionations of opposite signs for the hydrogen and oxygen isotopes (Meißner et al, 2014;Oerter et al, 2014). Thus, wherever weathered rocks constitute a large fraction of the soil volume, the isotopic composition of rock moisture should be measured as rock moisture could constitute a significant alternative plant water source.…”
Section: Rock Moisture As An Alternative Plant Water Source?mentioning
confidence: 99%
“…Although it cannot be ruled out that rock water in the carbonate-rich soil of Bowling et al (2017) was a significant source of water for trees or caused any unexpected isotope effects, the very clayey soil texture reported by Brooks et al (2010) seems less likely to contain a large rock water component. Oerter et al (2014) showed that cations adsorbed to clay minerals create isotopically organized hydration spheres of water around them and thereby sequester these water molecules away from the bulk water. However, even if the majority of the water contained in small pores is adsorbed water that does not interact with the more mobile water (the TWW hypothesis), in summer, when only water in small pores is accessible to the trees, there should be an isotopic match between soil pore and xylem water, unless H1 is not true and isotopic fractionation occurs during root uptake.…”
Section: Evidence Of Isotope Fractionation During Root Water Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…Condition (ii) is often neglected but is required due to the instantaneous nature of the sap flow 80 samples. As illustrated by Oerter and Bowen (2019), the lateral variability of the soil water isotopic composition profiles can become significant in the field and could have great implications on the representability and meaningfulness of isotopicderived estimate of RWU profiles.…”
Section: List Of Variables With Symbols and Unitsmentioning
confidence: 99%